Are commonly recommended dosages for vitamin D supplementation too low?: Vitamin D status and effects of supplementation on serum 25-hydroxyvitamin D levels : an observational study during clinical practice conditions - Leidig-Bruckner, Gudrun; Roth, Heinz Jürgen; Bruckner, Thomas; Lorenz, Angela; Raue, Friedhelm; Frank-Raue, Karin (Osteoporosis international, 2011)
Vitamin D deficiency is associated with increased fracture risk. The observational study aimed to investigate vitamin D status and supplementation in ambulatory patients. Only 20% of patients had optimal serum 25-hydroxyvitamin D [25(OH)D] levels. Commonly recommended dosages were insufficient to achieve clinically relevant increase of 25(OH)D levels. Higher dosages were safe and effective under clinical practice conditions.